Efficient Production of Epoxy‐Norbornane from Norbornene by an Engineered P450 Peroxygenase. (9th December 2022) - Yan, Yu; Zheng, Chenni; Song, Wei; Wu, Jing; Guo, Liang; Gao, Cong; Liu, Jia; Chen, Xiulai; Zhu, Meng; Liu, Liming
Abstract: Epoxy‐norbornane (EPO‐NBE) is a crucial building block for the synthesis of various biologically active heterocyclic systems. To develop an efficient protocol for producing EPO‐NBE using norbornene (NBE) as a substrate, cytochrome P450 enzyme from Pseudomonas putida (CYP238A1) was examined and its crystal structure (PDB code: 7X53) was resolved. Molecular mechanism analysis showed a high energy barrier related to iron‐alkoxy radical complex formation. Therefore, a protein engineering strategy was developed and an optimal CYP238A1 NPV variant containing a local hydrophobic "fence" at the active site was obtained, which increased the H2 O2 ‐dependent epoxidation activity by 7.5‐fold compared with that of CYP238A1 WT . Among the "fence", Glu255 participates in an efficient proton transfer system. Whole‐cell transformation using CYP238A1 NPV achieved an EPO‐NBE yield of 77.6 g ⋅ L −1 in a 30‐L reactor with 66.3 % conversion. These results demonstrate the potential of this system for industrial production of EPO‐NBE and provides a new biocatalytic platform for epoxidation chemistry. Abstract : Based on the resolved crystal structure (PDB code: 7X53), a protein engineering strategy was developed in CYP238A1 and an optimal CYP238A1 NPV variant containing a local hydrophobic "fence" at the active site was obtained, which increased the H2 O2 ‐dependent norbornene (NBE) epoxidation activity by 7.5‐fold compared with that of CYP238A1 WT and switched the monooxygenase mode to the peroxygenase mode.